2016
DOI: 10.1002/jctb.4898
|View full text |Cite
|
Sign up to set email alerts
|

Red mud as acidic sandy soil ameliorant: a microcosm incubation study

Abstract: BACKGROUND: Red mud is increasingly considered a valuable by-product requiring development of new re-use technologies instead of deposition as waste. This paper reports the results of a microcosm study aiming to reveal the beneficial effects of the Ajka red mud, as soil ameliorant, on a specific acidic sandy soil in eastern Hungary. RESULTS:The red mud amount mixed into the sandy soil ranged between 0 and 50%. The experiment was monitored by an integrated methodology combining physical and chemical methods wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
3
28
1
Order By: Relevance
“…+ -N and NO3 --N) and humus-content slightly decreased (Ujaczki et al, 2016a). EC and pH showed negative correlation, while nitrogen forms showed positive correlation with AWCD in our experiment (Suppl Table 2), thus the changes in the chemical composition of the soil do not explain the AWCD increase at low RM doses.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…+ -N and NO3 --N) and humus-content slightly decreased (Ujaczki et al, 2016a). EC and pH showed negative correlation, while nitrogen forms showed positive correlation with AWCD in our experiment (Suppl Table 2), thus the changes in the chemical composition of the soil do not explain the AWCD increase at low RM doses.…”
Section: Discussioncontrasting
confidence: 48%
“…Several case studies have demonstrated the applicability of red mud in soil amelioration and remediation, however, only a few have dealt with its effect on the soil biota, including the soil microorganisms (Lombi et al, 2002, Garau et al, 2007, Ujaczki et al, 2016a. In experiment "A" red mud (RM) at up to 20% had positive short term (3 months after treatment) effect on the microflora of an acidic sandy soil based on the AWCD values of the Biolog EcoPlate (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations